2021
DOI: 10.1021/acsbiomaterials.1c00486
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylated Gellan Gum/Poly-l-lysine Polyelectrolyte Complex Beads for Cell-Based Therapies

Abstract: Cell encapsulation strategies using hydrogel beads have been considered as an alternative to immunosuppression in cell-based therapies. They rely on layer-by-layer (LbL) deposition of polymers to tune beads' permeability, creating a physical barrier to the host immune system. However, the LbL approach can also create diffusion barriers, hampering the flow of essential nutrients and therapeutic cell products. In this work, the polyelectrolyte complex (PEC) methodology was used to circumvent the drawbacks of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…To get an idea about possible immune response that may be evoked by the fabricated nanocomposites scaffolds, immunocompatibility of the nonfunctionalized and functionalized PNF:Ch nanocomposites scaffolds was assessed using murine macrophages RAW 264.7 cells as per previous protocol. 80 In brief, 5 × 10 4 cells were seeded in a 24 well plate containing different scaffolds (size, 5 mm × 5 mm), where 250 ng of lipopolysaccharide (LPS) and nonstimulated tissue culture (NTC) were used as positive control and plate as negative control. After 24 and 48 h of treatment, conditioned media were collected and tested for the release of interleukin-1β (IL-1β) using an IL-1β ELISA kit according to the manufacturer's protocol (Invitrogen).…”
Section: Urease Immobilization Studiesmentioning
confidence: 99%
“…To get an idea about possible immune response that may be evoked by the fabricated nanocomposites scaffolds, immunocompatibility of the nonfunctionalized and functionalized PNF:Ch nanocomposites scaffolds was assessed using murine macrophages RAW 264.7 cells as per previous protocol. 80 In brief, 5 × 10 4 cells were seeded in a 24 well plate containing different scaffolds (size, 5 mm × 5 mm), where 250 ng of lipopolysaccharide (LPS) and nonstimulated tissue culture (NTC) were used as positive control and plate as negative control. After 24 and 48 h of treatment, conditioned media were collected and tested for the release of interleukin-1β (IL-1β) using an IL-1β ELISA kit according to the manufacturer's protocol (Invitrogen).…”
Section: Urease Immobilization Studiesmentioning
confidence: 99%
“…It is confirmed that EPL goes against bacteria through the membrane-lysis mechanism . To date, EPL has been developed for wound dressings, biomedical device coatings, food packaging, and so on. However, the physicochemical properties and stability issues limit their therapeutic application in the biomedical field due to their ionic nature . Especially, a large quantity of EPL addition can induce phase separation or color change.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, besides the programmed structure, the preparation material of hydrogels is also crucial for smart hydrogel actuators. It is well-known that polyelectrolyte materials are widely used in the construction of functional hydrogels due to the ionic bonds between cross-linked polymer chains. , Current studies revealed that the electrostatic interactions between polymer chains drive the polyelectrolytes to spontaneously aggregate and exhibit phase separation behavior, , and this phase separation structure enriches the deformation diversity of anisotropic hydrogels as an auxiliary structure . Moreover, ionic bonds are often used to impart excellent mechanical and self-healing properties to hydrogels , due to their reversible nature and wide strength distribution .…”
Section: Introductionmentioning
confidence: 99%